Diagnostic Approaches and Treatment Outcomes in Pediatric Thyroid Malignancies: A Systematic Review - Tomi Siagian (Jurnal Impresi Indonesia, 2026)
Thyroid cancer in children is rare but often diagnosed at an advanced stage. Although the prognosis is generally good, variations in diagnostic approaches and treatment strategies highlight the need for a comprehensive synthesis of current evidence specifically focused on the pediatric population. This systematic review aims to summarize and evaluate the available evidence regarding diagnostic approaches and treatment outcomes in pediatric thyroid cancer. A literature search was conducted in PubMed/MEDLINE, Scopus, and Embase in accordance with the PRISMA 2020 guidelines. Eligible studies were original clinical trials involving pediatric patients (<18 years) with thyroid cancer, reporting diagnostic modalities and/or treatment outcomes. Study selection, data extraction, and risk of bias assessment were performed independently by two reviewers. Due to heterogeneity between studies, a qualitative narrative synthesis was performed. Five retrospective cohort studies met the inclusion criteria. Ultrasonography and fine-needle aspiration biopsy were consistently used as the primary diagnostic tools in all studies. Surgery, primarily total thyroidectomy with or without lymph node dissection, was the primary treatment. Radioactive iodine therapy is generally given to intermediate- and high-risk patients, while some low-risk patients achieve good outcomes without it. Survival and remission rates are high, although recurrence is associated with tumor characteristics such as multifocality, bilaterality, and lymph node involvement. Treatment-related complications are rare. Current evidence supports a staged diagnostic approach and risk-adapted treatment strategies for pediatric thyroid cancer.